Exhaust port flow study on various cylinder head using flowbench - Mohd Firdaus Naqiuddin, Che Pa (2008)
This is a project about the study of exhaust port flow for Proton 4G92 and Toyota 4 AGE cylinder head. It is a testing using SF-1020 Air Flowbench machine that has been used to determine the air flow between the original exhaust port and modified exhaust port. In this study, an experiment approach has been performed to investigate the flow distribution of exhaust gases that will affect the performance of the engine by the design of exhaust port shape for cylinder head. The modification to the cylinder head such as eliminates the valve guide, porting and polishing has been done as a parameter during this experiment. Both cylinder heads are adapted with modification and it gives positive results of air flow increment for every modification applied. The highest air flow is in Proton 4G92 cylinder head and it improves the power and performance of the engine.